The Cambridge handbook of sociolinguistics - Mesthrie, Rajend (Cambridge : Cambridge University Press, 2011)
'The most comprehensive overview available, this handbook is an essential guide to sociolinguistics today. Reflecting the breadth of research in the field, it surveys a range of topics and approaches in the study of language variation and use in society. As well as linguistic perspectives, the handbook includes insights from anthropology, social psychology, the study of discourse and power, conversation analysis, theories of style and styling, language contact and applied sociolinguistics. Language practices seem to have reached new levels since the communications revolution of the late twentieth century. At the same time face-to-face communication is still the main force of language identity, even if social and peer networks of the traditional face-to-face nature are facing stiff competition of the Facebook-to-Facebook sort. The most authoritative guide to the state of the field, this handbook shows that sociolinguistics provides us with the best tools for understanding our unfolding evolution as social beings.'--Publisher's website.
Introduction: the sociolinguistic enterprise / Rajend Mesthrie -- Foundations of sociolinguistics. Power, social differentiation and language / John Baugh -- Linguistic anthropology / Alessandro Duranti -- Social psychology and language / Peter Robinson and Abigail Locke -- Orality and literacy in sociolinguistics / Lowry Hemphill -- Sign languages / Ceil Lucas and Bob Bayley -- Interaction, style and discourse. Conversation and interaction / Cynthia Gordon -- Pragmatics and discourse / Jan Blommaert -- The sociolinguistics of style / Nikolas Coupland -- Social and regional dialectology. Language, class and status / Gregory Guy -- Language and region / Bill Kretzschmar -- Language and place / Barbara Johnstone -- Language, gender, sexuality / Natalie Schilling -- Language and ethnicity / Carmen Fought -- Multilingualism and language contact. Multilingualism and multiculturalism / Ana Deumert -- Pidgins, creoles and other contact varieties / John Singler and Silvia Kouwenberg -- Code switching / Pieter Muysken -- Language maintenance, shift and endangerment / Nicholas Ostler -- Colonisation, globalisation and world Englishes / Edgar Schneider -- Applied sociolinguistics. Language planning and policy / James Tollefson -- Language and the law / Diana Eades -- Language and the media / Susan McKay --Language and education / Christopher Stroud and Kathleen Heugh.
Includes bibliographical references (p. [440]-522) and index.
Keywords: Sociolinguistics